Åbo domkyrkas första murade sakristia - Drake, Knut (Hikuin, 2006)
The First Stone Sacristy in Turku Cathedral By Knut Drake Turku Cathedral was consecrated in 1300. The church of that time was probably a modest wooden building, which was not replaced until in the early 15th century by the nave of the brick-built cathedral that is still standing. Already during the 14th century, a few attempts were made to begin building a stone church to replace the old wooden one. The result of the first attempt was a greystone sacristy, the remains of which were discovered during building archaeological investigations in the 1920s. According to the investigations’ supervisor, Juhani Rinne, the remains once belonged to a building which was made entirely of natural stone. Its southern gable end should still be visible in the north wall of the current church’s nave. In the upper part of the greystone wall is an opening measuring 100 x 70 cm, which according to Rinne would have led to the old sacristy’s attic. The original doorway to the sacristy was torn down in 1805 and replaced with a granite portal. Rinne thought that the original portal was also built of natural stone. In this article, I demonstrate that Rinne’s interpretations were erroneous. Only the western section of the stonework visible in the current nave’s north wall was part of the old sacristy’s gable wall. The opening at the top of the masonry section does not belong to the gable; it functioned as a doorway to the attic of the new sacristy built during the following building phase. The first stone sacristy was accessed through a brick-built portal with a pointed arch. A limestone slab discovered in the 1920s has apparently served as a socle in this first brick portal, as its moulding corresponds to the bricks from the portal’s jamb. Turku Cathedral’s sacristy is mentioned in a document from 1291. However, this need not be a reference to the stone sacristy discussed here, as it could also refer to a wooden sacristy. Because there is no other evidence that could be used for dating, the construction date of the stone sacristy remains an open question.